La dislocation d’un SA superlatif relatif d’infériorité : un cas particulier ? - Nowakowska, Aleksandra (Studia Romanica Posnaniensia, 2012)
This article presents a thorough study of dislocation of superlative inferiority adjective dialogic function. The hypothesis of work stipulates that the dislocation is dialogic because the dislocated theme implies a relationship with a prior utterance by another enunciation. This relationship between two utterances is based on a comparison and makes dislocation a dialogic marker.